Valores suéricos y recambio de hormonas tiroideas en el geronte - Degrossi, Osvaldo Jorge; Diez, F.; Carneiro, Laureano; Casas, O.I. de; Cima, M.E.; Almeida, C.A.; Scornavacchi, J.C.; Mollerach, F.E. (Comisión Nacional de Energía Atómica (CNEA), 1980)
Fil:Degrossi, O.J. Comisión Nacional de Energía Atómica (CNEA). República Argentina